COMPARATIVE ANALYSIS OF THE VIEWS OF EASTERN AND WESTERN THINKERS ON ALIENATION (TAMADDUN NURI JURNALI, 2025)
The article provides a comparative analysis of the views of Western and Eastern thinkers on the problem of alienation. In Western philosophy, the ideas of such thinkers as Karl Marx, Emile Durkheim and Max Weber on alienation are studied, and in Eastern philosophy, the views of Confucius, Lao-tzu, Jalaluddin Rumi and Al-Farabi are studied.